Dimensional Analysis and Scale-up in Chemical Engineering - Zlokarnik, Marko (Springer Berlin Heidelberg, 1991)
Contemporary Chemical Process Engineers face complex design and research problems. Temperature-dependent physical properties and non-Newtonian flow behavior of substances in a process cannot be predicted by numerical mathematics. Scaling-up equipment for processing can often only be done with partial similarity methods. Standard textbooks often neglect topics like dimensional analysis, theory of similarity and scale-up. This book fills this gap! It is aimed both at university students and the process engineer. It presents dimensional analysis very comprehensively with illustrative examples of mechanical, thermal and chemical processes.